INTRODUCTION TO ENGLISH LANGUAGE TEACHING - Beshlei, Olga (Видавничий дім “РОДОВІД”, 2020)
The proposed guide is intended for the 1st year students of the Faculty of Foreign Languages, speciality 014 - Secondary Education within the "Introduction to the Specialty" educational course. The material is presented in the form of 13 sections, which correspond to the number of lectures and highlight general issues of effective organization of the educational process in the English language class. The subject of the course covers the following aspects: the role of the teacher; needs and expectations of students; their support and encouragement to study; functional approach to learning a foreign language; formation of skills and competencies within the communicative context; types and forms of work and control of learned knowledge in class; the future of English language teaching. The manual aims to form a sustainable interest of students in future pedagogical activity by simultaneously presenting theoretical provisions and the possibility of their practical application through the implementation of interactive tasks, conducting independent searches, working with video materials, as well as the constant use of reflective techniques and knowledge acquisition tactics.
ELT